2014
DOI: 10.9745/ghsp-d-13-00141
|View full text |Cite
|
Sign up to set email alerts
|

Taking knowledge for health the extra mile: participatory evaluation of a mobile phone intervention for community health workers in Malawi

Abstract: A participatory evaluation process called Net-Map showed that providing community health workers (CHWs) with mobile phones and essential technical information changed CHWs, from passive recipients of information with little influence to active information agents who sought and provided information to improve health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…The different data sets allow for triangulation between network structures and narratives (Gamper et al 2012). There are many descriptions of data collection processes using the Net-Map tool (e.g., Hauck 2010, Schiffer and Hauck 2010, Aberman et al 2012, Bell et al 2013, Campbell et al 2014, Stein et al 2014, therefore, we only briefly describe it here.…”
Section: General Description Of Data Collection and Analysismentioning
confidence: 99%
“…The different data sets allow for triangulation between network structures and narratives (Gamper et al 2012). There are many descriptions of data collection processes using the Net-Map tool (e.g., Hauck 2010, Schiffer and Hauck 2010, Aberman et al 2012, Bell et al 2013, Campbell et al 2014, Stein et al 2014, therefore, we only briefly describe it here.…”
Section: General Description Of Data Collection and Analysismentioning
confidence: 99%
“… 3 Several studies in Malawi have shown that mobile phones have the capacity to increase communication with distant communities and strengthen health programs. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…The tool addresses several problems that may occur during conventional interviews, such as reaching transparency and common understanding through visualizing the situation, overcoming shyness or the will to talk and creating a comfortable atmosphere that keeps the participants involved, which in the end improves not only social learning but also the quality of the interview data (Campbell et al, 2014;Schiffer and Waale, 2008).…”
Section: Discussionmentioning
confidence: 99%